2021
DOI: 10.1111/iwj.13695
|View full text |Cite
|
Sign up to set email alerts
|

What COVID‐19 taught us: New opportunities and pathways from telemedicine and novel antiseptics in wound healing

Abstract: The COVID‐19 pandemic deeply impacted the capacity of the health systems to maintain preventive and curative services, especially for the most vulnerable populations. During the pandemic, the wound healing centres in Italy assisted a significant reduction of the frequency of their hospital admission, since only urgencies, such as severe infections or wound haemorrhagic complications, were allowed to the hospital. The aim of this multidisciplinary work is to highlight the importance of a new pathway of wound ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eligibility process applied to the selected references, after the elimination of the duplicated ones, returned 39 works [ 5 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ], including a review focused on the relationship between telemedicine and radiotherapy [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The neurology sector has also recorded an important use of applications in Parkinson’s disease [ 44 ]; in the use of telemedicine for the multidisciplinary assessment of patients with Amyotrophic Lateral Sclerosis [ 47 ]; for multiple sclerosis [ 28 ]; for a headache specialist center; and in applications of telephysiotherapy [ 47 ]. The overview also reported the application of telemedicine in other sectors less common in telemedicine solutions, such as: colorectal surgery [ 24 ]; wound care [ 20 ]; urological benign diseases [ 32 ]; endocrinology [ 34 ]; inflammatory bowel disease [ 37 ]; teleconsulting with a bariatric center; and chronic liver disease [ 42 ]. There has been the use of systems, in some simple cases, such as telephony [ 32 , 50 ], and in other more complex cases, such as specialized servers [ 53 ], which have allowed the application of telemedicine with success.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that known mucolytic and expectorant drugs also do not provide high speed and efficiency in dissolving and removing thick and sticky pus in various purulent diseases [48]. All this justifies the need to search for new and more effective "antipurulent" drugs [49].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, managing DFUs from the beginning at the first examination to the end must be specified in every health system. 23,24 According to the studies, despite establishing diabetes management guidelines, it seems that without suitable education, training, and proper protocols, achieving our goals in DFUs management is impossible. Therefore, to solve this issue, the International Diabetic Foot Care Group (IDFCG) and diabetic foot international introduced a new, easy-to-perform method called the Fast-Track Pathway for DFUs.…”
Section: Fast-track Pathway Goalsmentioning
confidence: 99%